Impact of Concurrent PIK3CA Mutations on Response to EGFR Tyrosine Kinase Inhibition in EGFR-Mutant Lung Cancers and on Prognosis in Oncogene-Driven Lung Adenocarcinomas. Issue 12 (December 2015) - Eng, Juliana; Woo, Kaitlin M.; Sima, Camelia S.; Plodkowski, Andrew; Hellmann, Matthew D.; Chaft, Jamie E.; Kris, Mark G.; Arcila, Maria E.; Ladanyi, Marc; Drilon, Alexander
Abstract : Introduction: In patients with epidermal growth factor receptor ( EGFR )-mutant or KRAS -mutant lung adenocarcinomas, the prognostic impact of a concurrent PIK3CA mutation remains unclear. Although preclinical data suggest that sensitivity to EGFR tyrosine kinase inhibition (TKI) is decreased in EGFR -mutant lung cancers also harboring a PIK3CA mutation, this interaction has not been explored clinically. Methods: Patients with lung adenocarcinomas harboring a PIK3CA mutation concurrent with a separate driver mutation were identified through mutational hotspot testing, multiplex sizing assays, and fluorescence in situ hybridization. Overall survival and outcomes with EGFR TKI monotherapy ( EGFR -mutant) were estimated using Kaplan–Meier methods and compared between double-mutant ( EGFR -mutant or KRAS -mutant, concurrent PIK3CA -mutant) and single-mutant patients ( EGFR -mutant or KRAS -mutant, PIK3CA wild-type) using log-rank tests. Results: In EGFR -mutant and KRAS -mutant lung cancers, a concurrent PIK3CA mutation was associated with a decrease in median overall survival: 18 versus 33 months ( EGFR double mutant, n = 10 versus single mutant, n = 43, p = 0.006), and 9 versus 16 months ( KRAS double mutant, n = 16 versus single mutant, n = 47, p = 0.020). In EGFR -mutant lung cancers, a concurrent PIK3CA mutation did not impact benefit from EGFR TKI monotherapy. Single versus double mutant: objective response rate, 83% (n = 29) versus 62% (n = 6, p = 0.80); median time to progression, 11 (n = 29) versus 8 months (n = 6, p = 0.84); and median duration of TKI therapy, 15 (n = 32) versus 15 months (n = 10, p = 0.65). Conclusion: A concurrent PIK3CA mutation is a poor prognostic factor in patients with advanced EGFR -mutant or KRAS -mutant lung adenocarcinomas. There was no evidence that clinical benefit from EGFR TKI monotherapy is affected by a concurrent PIK3CA mutation in EGFR -mutant lung cancers.